Does That Count? - Gloria Ladson-Billings (Aggie STEM, 2021)
Many mathematics educators feel that their work is not amenable to questions of diversity, equity, or justice. However, this article argues that “numbers” are not neutral. What we count and how we count are directly related to basic issues of human difference and social disparity. It also argues that mathematics knowledge and skills are fundamental to civic participation and engagement. Mathematics educators do have a stake in helping us achieve equitable social outcomes.